Potential Use of Probiotic Consortium Isolated from Kefir for Textile Azo Dye Decolorization - Ayed, Lamia; Zmantar, Tarek; Bayar, Sihem; Cheref, Abdelkrim; Achour, Sami; Ben Mansour, Hedi; Mzoughi, Ridha El (Journal of microbiology and biotechnology, 2019)
Azo dyes are recalcitrant pollutants, which are toxic, carcinogenic, mutagenic and teratogenic, that constitute a significant burden to the environment. The decolorization and the mineralization efficiency of Remazol Brillant Orange 3R (RBO 3R) was studied using a probiotic consortium ( and ). Biodegradation of RBO 3R (750 ppm) was investigated under shaking condition in Mineral Salt Medium (MSM) solution at pH 11.5 and temperature 25°C. The bio-decolorization process was further confirmed by FTIR and UV-Vis analysis. Under optimal conditions, the bacterial consortium was able to decolorize the dye completely (>99%) within 12 h. The color removal was 99.37% at 750 ppm. Muliplex PCR technique was used to detect the . Using phytotoxicity, cytotoxicity, mutagenicity and biototoxicity endpoints, toxicological studies of RBO 3R before and after biodegradation were examined. A toxicity assay signaled that biodegradation led to detoxification of RBO 3R dye.